Pemodelan Dan Simulasi Motor Dc Dengan Kendali Model Predictive Control (MPC) - Sinuraya, Enda Wista (Departemen Teknik Elektro, Universitas Diponegoro, 2012)
Motors are devices that convert electrical energy into mechanical energy. The D.C. motors that runs on direct current (DC) electricity convert electrical energy into rotational energy. That rotational energy is then used to lift things, propel things, turn things, etc. the implementation model predictive control for controlling a D.C motor can change system’s output before setpoint be changed. Keyword: D.C Motor, model predictive control (MPC), setpoint